1998
DOI: 10.1021/cm980028y
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Compact Hydrous Aluminum Sulfate Thin Films on Titania Particles Coated with Organic Self-Assembled Monolayers

Abstract: An organic self-assembled monolayer (SAM) was deposited on submicron-sized pigmentgrade TiO 2 particles to create a highly hydrophilic surface comprised of sulfonate groups. Hydrous aluminum-containing thin films were uniformly deposited on the powder from aqueous solutions at 60-80 °C. The as-deposited films were in the form of boehmite (AlO(OH)) or hydrous Al sulfate, depending on the Al salts used in the starting solution. AlCl 3 solutions gave rise to porous films of needlelike crystalline boehmite, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…9 -13 Raviendra and Sharma 9 have reported initial growth rates of 1-2 m⅐h -1 with growth virtually stopping at thicknesses of 0.7-0.8 m. Using various solution conditions, Supothina and De Guire 12 have grown SnO 2 films on self-assembled monolayers (SAMs) at initial rates of ϳ10 nm⅐h Ϫ1 , decreasing with time to ϳ3 nm⅐h Ϫ1 , to maximum thicknesses of 60 -70 nm. Similar decreases in film growth rate with time are also observed in the deposition of TiO 2 , 14 ZrO 2 , 15 and aluminum basic sulfate 16 films from aqueous media. Shirahata et al 17 have reported decreasing growth rates for SnO 2 precursor films from toluene solutions.…”
Section: Introductionsupporting
confidence: 73%
“…9 -13 Raviendra and Sharma 9 have reported initial growth rates of 1-2 m⅐h -1 with growth virtually stopping at thicknesses of 0.7-0.8 m. Using various solution conditions, Supothina and De Guire 12 have grown SnO 2 films on self-assembled monolayers (SAMs) at initial rates of ϳ10 nm⅐h Ϫ1 , decreasing with time to ϳ3 nm⅐h Ϫ1 , to maximum thicknesses of 60 -70 nm. Similar decreases in film growth rate with time are also observed in the deposition of TiO 2 , 14 ZrO 2 , 15 and aluminum basic sulfate 16 films from aqueous media. Shirahata et al 17 have reported decreasing growth rates for SnO 2 precursor films from toluene solutions.…”
Section: Introductionsupporting
confidence: 73%
“…8 These experiments convincingly demonstrated that: (i) simple hydrocarbon SAMs (OTS) and SAMs bearing thioacetate (TA) functionality can be applied to TiO 2 powder; (ii) on the TiO 2 particles, the OTS coating was organized into a more close-packed organic film than was the TA-SAM; (iii) the TA-SAM on the TiO 2 particles can be oxidized to a sulfonate-bearing SAM, as had been described for SAM arrays on flat substrates. 8 These experiments convincingly demonstrated that: (i) simple hydrocarbon SAMs (OTS) and SAMs bearing thioacetate (TA) functionality can be applied to TiO 2 powder; (ii) on the TiO 2 particles, the OTS coating was organized into a more close-packed organic film than was the TA-SAM; (iii) the TA-SAM on the TiO 2 particles can be oxidized to a sulfonate-bearing SAM, as had been described for SAM arrays on flat substrates.…”
Section: B Characteristics Of Sams On Powdersmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] During heat treatments of these films, the pyrolysis of the SAM is an important issue, mainly because of its potential for disruption of the adherence, continuity, or uniformity of the oxide films. [2][3][4][5][6][7][8] During heat treatments of these films, the pyrolysis of the SAM is an important issue, mainly because of its potential for disruption of the adherence, continuity, or uniformity of the oxide films.…”
Section: Introductionmentioning
confidence: 99%
“…The SAMs are ultrathin (1.5-3.0 nm) [20] ordered arrays of closely packed long-chain hydrocarbon molecules composed of base and tail groups at the opposite ends of a hydrocarbon chain. The SAMs preferentially attach to a surface, uniformly exposing the tail group to achieve surface functionalization.…”
Section: Introductionmentioning
confidence: 99%